An early post-transplant relapse prediction score in multiple myeloma: a large cohort study from the chronic malignancies working party of EBMT - Beksac, Meral; Iacobelli, Simona; Koster, Linda; Cornelissen, Jan; Griskevicius, Laimonas; Rabin, Neil K; Stoppa, Anne Marie; Meijer, Ellen; Mear, Jean-Baptiste; Zeerleder, Sacha; Mayer, Jiri; Fenk, Roland; et al. (Bone marrow transplantation, 2023)
Early relapse (ER) following Autologous Hematopoietic Cell Transplantation (AHCT) confers a poor prognosis. We therefore developed a novel scoring system to predict ER. A total of 14,367 AHCT-1 patients were transplanted between 2014 and 2019, and were conditioned with Melphalan 200 mg/m2 (Mel200) (n = 7228; 2014-2017) (training cohort); Mel200 (n = 5616; 2018-2019) or Mel140 (n = 1523; 2018-2019) (validation cohorts). PFS-12 and the Cumulative Incidence of Relapse at 12 months were 84.1% and 14.7% (training Mel200), 87.2% and 11.6% (validation Mel200), and 80.3% and 16.9% (validation Mel140), respectively. The points in the risk score were: 0, 1,2 for ISS stages I, II, and III; Disease status: 0 (CR/VGPR); 1 (PR); 2 (SD/MR); 4 (Relapse/Progression); and 1 for Karnofsky ≤ 70. The distribution of scores: 0 (24%), 1 (33.9%), 2 (29.6 %), 3 (9.5%), and ≥4 (2.7%). The score separated PFS-12, with the lowest risk group (n = 1752) having a PFS-12 of 91.7% and the highest risk group (n = 195) 57.1%. This also applied in cytogenetically high-risk patients. If the pre-score baseline risks are 15% (standard risk) and 25% (high-risk), a score of ≥4 confers calculated risks of 38% and 54%, respectively. This novel EBMT ER score, therefore, allows for the identification of five discrete prognostic groups.
Keywords: Hematopoietic Stem Cell Transplantation; Multiple Myeloma; mnohočetný myelom; Cohort Studies; příprava pacienta k transplantaci; transplantace hematopoetických kmenových buněk; Melphalan; lokální recidiva nádoru; autologní transplantace; Humans; melfalan; Transplantation Conditioning; Transplantation, Autologous; lidé; Neoplasm Recurrence, Local; kohortové studie